The Emerald handbook of ICT in tourism and hospitality - Hassan, Azizul; Sharma, Anukrati (Emerald Publishing Limited, 2020)
The Emerald Handbook of ICT in Tourism and Hospitality examines the immense, widespread and ongoing changes that digital technologies are having on the tourism and hospitality industries globally. An international range of contributors present key research findings, in-depth case studies and discussion of the future implications stemming from technologies changes and developments across a number of core themes effecting these industries, including destination promotion, marketing contexts, service promotion and smart city involvement. Chapters explore new developments on a wide range of contemporary issues, including: ICT, sustainable development and implications for the tourism industry the role of mobile technology for tourism development influencer marketing for tourism and hospitality online tracking factors influencing Generation Y tourism choices cross country cases of ICT application in tourism and hospitality. The Emerald Handbook of ICT in Tourism and Hospitality is aimed primarily at global tourism academics and researchers, however graduate students of tourism and academics will also find this book to be of interest.
Includes index.
Keywords: Hospitality industry -- Data processing.; Tourism -- Data processing.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality industry.; elektronické knihy; electronic books